Design and characterization of millimeter wave planar reflectarray antenna for 5G communication systems. Issue 9 (25th April 2019) - Inam, Muhammad; Dahri, Muhammad Hashim; Jamaluddin, Mohd Haizal; Seman, Norhudah; Kamarudin, Muhammad Ramlee; Sulaiman, Noor Hafizah
Abstract: This work provides design and characterization of millimeter wave reflectarray antenna based on unit cells as well as periodic reflectarray design at 26 GHz. Diverse unit cell design configurations have been investigated based on simulations and scattering parameter measurements for feasibility of designing an optimum performance 5G reflectarray antenna. It has been demonstrated that the rectangular patch element provided minimum reflection loss of 1.02 dB and maximum bandwidth of 560 MHz. However, the phase error for rectangular patch element was observed to be 80°, which is much higher as compared to 10° and 13° in the case of rectangular ring and circular ring elements respectively. Periodic reflectarray antennas were also designed with main beam focused at 40° in the azimuth plane achieved with tilted array instead of using an offset feed. Radiation pattern measurements were carried out for further characterization where a maximum gain of 26.7 dB was provided by reflectarray designed with circular ring elements with variable radius. On the other hand, rectangular patch element array provided higher 1 dB gain drop bandwidth of 13.6% as compared to circular ring element reflectarray, which demonstrated a bandwidth of 13.1%. However, side lobe levels were observed to be higher at −18.4° for rectangular patch element reflectarray as compared to −19.4° in the case of circular ring elements based reflectarray antenna.